Coronavirus pandemic, remote learning and education inequalities - Luca Bonacini; Marina Murat (Global Labor Organization (GLO), 2021)
By using PISA 2018 data, we investigate the associations between digital divides and educational inequalities in France, Germany, Italy, Spain and the United Kingdom. We find strong and significant cognitive losses of students lacking the resources needed to learn remotely; everything else given, they range from 25 to 70 percent of a school year. In Germany, Italy and France, where tracking between schools starts earlier, digital gaps are strongly associated with school types. They are also wider in urban areas, where the use of ICT resources is more widespread. Grades repetition in Spain is associated with the digital divide, while family characteristics matter in the United Kingdom. In the longer run, students who cannot learn remotely are more likely to repeat grades and end their education early, especially where grades repetition is more common: Spain, Germany, and Italy. Education policies should be designed accordingly.
Keywords: I21; I24; H52; 330; Digital divide; education inequalities; educational systems; remote learning; PI